4-Anilinoquinazoline-based benzenesulfonamides as nanomolar inhibitors of carbonic anhydrase isoforms I, II, IX, and XII: design, synthesis, in-vitro, and in-silico biological studies. (31st December 2022) - Nada, Hossam; Elkamhawy, Ahmed; Abdellattif, Magda H.; Angeli, Andrea; Lee, Chang Hoon; Supuran, Claudiu T.; Lee, Kyeong
Abstract: Human carbonic anhydrase inhibitors (hCAIs) are a key therapeutic class with a multitude of novel applications such as anticonvulsants, topically acting antiglaucoma, and anticancer drugs. Herein, a new series of 4-anilinoquinazoline-based benzenesulfonamides were designed, synthesised, and biologically assessed as potential hCAIs. The target compounds are based on the well-tolerated kinase scaffold (4-anilinoquinazoline). Compounds 3a (89.4 nM), 4e (91.2 nM), and 4f (60.9 nM) exhibited 2.8, 2.7, and 4 folds higher potency against hCA I when compared to the standard (AAZ, V ), respectively. A single digit nanomolar activity was elicited by compounds 3a (8.7 nM), 4a (2.4 nM), and 4e (4.6 nM) with 1.4, 5, and 2.6 folds of potency compared to AAZ (12.1 nM) against isoform hCA II, respectively. Structure-activity relationship (SAR) and molecular docking studies validated our design approach that revealed highly potent hCAIs.